Moderating Role of Absorptive Capacity between Entrepreneurial Orientation and Technological Innovation Capabilities - Mohd Noor, Nor Azila; Ahmed Aljanabi, Abdul Qadir Rahomee (International Review of Management and Marketing, 2016)
The present study purposes to examine the moderating role of absorptive capacity on the relationship between entrepreneurial orientation and technological innovation capabilities among small and medium enterprises in the construction industry. Due to the critical role of SMEs in construction industry, the purpose of this article is to examine to what extent the externally generated knowledge manifested in absorptive capacity can strengthen the relationship between entrepreneurial orientation and technological innovation capabilities. To validate the proposed model, self-administered questionnaire were conducted to gather data from SMEs owners, 249 questionnaires returned and used for statistical analysis out of 278 distributed. The outcomes of present research reflect that both of absorptive capacity and entrepreneurial orientation have significant effects on technological innovation capabilities. Furthermore, the results indicate the moderating role of absorptive capacity on the nexus between entrepreneurial orientation and technological innovation capabilities. Keywords: absorptive capacity, entrepreneurial orientation, technological innovation capabilities. JEL Classification: M31